MERS-CoV spike nanoparticles protect mice from MERS-CoV infection. Issue 12 (14th March 2017) - Coleman, Christopher M.; Venkataraman, Thiagarajan; Liu, Ye V.; Glenn, Gregory M.; Smith, Gale E.; Flyer, David C.; Frieman, Matthew B.
Abstract: The Middle East respiratory syndrome coronavirus (MERS-CoV) was first discovered in late 2012 and has gone on to cause over 1800 infections and 650 deaths. There are currently no approved therapeutics or vaccinations for MERS-CoV. The MERS-CoV spike (S) protein is responsible for receptor binding and virion entry to cells, is immunodominant and induces neutralizing antibodies in vivo, all of which, make the S protein an ideal target for anti-MERS-CoV vaccines. In this study, we demonstrate protection induced by vaccination with a recombinant MERS-CoV S nanoparticle vaccine and Matrix-M1 adjuvant combination in mice. The MERS-CoV S nanoparticle vaccine produced high titer anti-S neutralizing antibody and protected mice from MERS-CoV infection in vivo .